MODEL PENINGKATAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR BERBASIS MOTIVASI INTRINSIK DAN ORGANIZATIONAL JUSTICE PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PONOROGO - Yuniarko, Dhevit; Suwardi, Suwardi; Winarni, Liliek (Master of Public Administration, Universitas Slamet Riyadi, 2020)
The problem of decreasing absenteeism towards the performance of the State CivilApparatus (ASN) caused by declining intrinsic motivation originating from himself andorganizational justice is still an interesting thing to study. This study aims to determinethe Model of Improvement of Organizational Citizenship Behavior Based on IntrinsicMotivation and Organizational Justice in the Population and Civil Registration Office ofPonorogo Regency. This research was conducted at the Population and Civil RegistryOffice of Ponorogo Regency and the data obtained through a questionnaire along with aninterview guide distributed to 42 respondents and analyzed using Path Analysis. Basedon the results of the study, it can be concluded that the increase in OrganizationalCitizenship Behavior can be done by increasing Intrinsic Motivation and OrganizationalJustice by being mediated by Affective Commitments. Intrinsic motivation and goodorganizational justice will encourage increased affective commitment which willultimately improve employee performance through Organizational Citizenship Behavior.Employees who always have high intrinsic motivation will have high performance. Themore employees feel they get organizational justice in an organization that is able toabsorb, understand and implement it, the higher the employee's performance. Thelimitation of this study raises suggestions for future research, namely the need forappropriate moderation variables to encourage the strengthening of the influence ofvariables on performance.